Early prone positioning in acute respiratory distress syndrome related to COVID-19: a propensity score analysis from the multicentric cohort COVID-ICU network—the ProneCOVID study - Christophe Le Terrier; Florian Sigaud; Said Lebbah; Luc Desmedt; David Hajage; Claude Guérin; Jérôme Pugin; Steve Primmaz; Nicolas Terzi; COVID-ICU Group on behalf of the REVA Network and the COVID-ICU Investigators (Critical Care, 2022)
Abstract Background Delaying time to prone positioning (PP) may be associated with higher mortality in acute respiratory distress syndrome (ARDS) due to coronavirus disease 2019 (COVID-19). We evaluated the use and the impact of early PP on clinical outcomes in intubated patients hospitalized in intensive care units (ICUs) for COVID-19. Methods All intubated patients with ARDS due to COVID-19 were involved in a secondary analysis from a prospective multicenter cohort study of COVID-ICU network including 149 ICUs across France, Belgium and Switzerland. Patients were followed-up until Day-90. The primary outcome was survival at Day-60. Analysis used a Cox proportional hazard model including a propensity score. Results Among 2137 intubated patients, 1504 (70.4%) were placed in PP during their ICU stay and 491 (23%) during the first 24 h following ICU admission. One hundred and eighty-one patients (36.9%) of the early PP group had a PaO2/FiO2 ratio > 150 mmHg when prone positioning was initiated. Among non-early PP group patients, 1013 (47.4%) patients had finally been placed in PP within a median delay of 3 days after ICU admission. Day-60 mortality in non-early PP group was 34.2% versus 39.3% in the early PP group (p = 0.038). Day-28 and Day-90 mortality as well as the need for adjunctive therapies was more important in patients with early PP. After propensity score adjustment, no significant difference in survival at Day-60 was found between the two study groups (HR 1.34 [0.96–1.68], p = 0.09 and HR 1.19 [0.998–1.412], p = 0.053 in complete case analysis or in multiple imputation analysis, respectively). Conclusions In a large multicentric international cohort of intubated ICU patients with ARDS due to COVID-19, PP has been used frequently as a main treatment. In this study, our data failed to show a survival benefit associated with early PP started within 24 h after ICU admission compared to PP after day-1 for all COVID-19 patients requiring invasive mechanical ventilation regardless of their severity.